How to use Alternative Medicine and Natural Medicine in the 21st Century Part III (London Journal of Medical and Health Research, 2025)
Alternative and Natural Medicine are nonmedical techniques and therapies that help a client heal faster and use non-medication for the mind, body, and soul. Also, Holistic perspectives provide a framework for understanding how sentient beings, including humans, perceive and interact with the world. In the Holistic study, these guidelines are for us to follow, and they are the: Six Universal Reality Dimensions, as presented in the Theory of Holistic Perspective, they describe the fundamental aspects through which all sentient beings perceive and engage with reality.This article will continue from Article PT II the modalities, perspective, and theory of alternative. Also, the discussion will have a plethora of TCM and Herbology medicine.
Keywords: Risk factors; Surgery; mortality; Trauma; Chest; Wound.